2021
DOI: 10.1021/acs.biochem.1c00228
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Potential Inhibitor of the FIV p24 Capsid Protein and Characterization of Its Binding Site

Abstract: RID-AGE-Risk factors and molecular determinants of aging-related,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 73 publications
0
12
0
Order By: Relevance
“…We have recently demonstrated the binding and inhibitory effect of 696 on FIV capsid assembly in vitro [ 27 ]. Thus, we investigated the interaction of 696 with HIV-1 CA by microscale thermophoresis (MST).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently demonstrated the binding and inhibitory effect of 696 on FIV capsid assembly in vitro [ 27 ]. Thus, we investigated the interaction of 696 with HIV-1 CA by microscale thermophoresis (MST).…”
Section: Resultsmentioning
confidence: 99%
“…The chemical synthesis of these molecules followed the previously reported procedures [ 28 , 30 , 33 , 38 , 39 ]. Synthesis and in-depth characterization of the two compounds 696 [ 27 ] and 314, which are thoroughly analyzed in this study, are available as supporting information.…”
Section: Methodsmentioning
confidence: 99%
“…Compound 696 A screening of an in-house library of 400 compounds identified a feline immunodeficiency virus (FIV) assembly inhibitor, named 696 (Table 1) [73]. The authors also identified the binding pocket within FIV CA where 696 binds.…”
Section: Ck026 and I-xw-053mentioning
confidence: 99%
“…It has therefore been inferred that the FIV core had similar assembly constraints, and that its formation is likely to involve pentamers and hexamers of FIV CA. However, the structures of these FIV oligomers have yet to be identified [42].…”
Section: Fiv Camentioning
confidence: 99%
“…Interestingly, GS-6207 binds at the CA/CA interface within HIV-1 CA hexamers and has been optimized from lead molecules using the structural data available on these hexamers [14,52,53]. For FIV, assembly inhibitors have recently been identified that bind the same region of CA, which seems to be similarly able to interact with feline nucleoporins [42,54] and thus represent an interesting therapeutic target. Obtaining structural data on FIV CA oligomers will therefore be of prime importance for the optimization of these compounds towards efficient anti-FIV molecules.…”
Section: Fiv Camentioning
confidence: 99%